Market research analysis of jack bean-based tempeh using consumer preferences and conjoint analysis method in Banda Aceh and Aceh Besar - Ulya, Zaudhatul; Lufika, Raihan Dara; Zubir, Awal Aflizal; Mandira, Ade Surya; Mailida, Sintia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Tempeh is one of the most commonly consumed plant-based protein sources in Indonesia. However, heavy reliance on imported soybeans undermines national food security. As an alternative, jack bean-based tempeh (Canavalia ensiformis) offers promising potential due to its high protein and antioxidant content. Currently, this product is still in development and not widely available in the Aceh region. Initial production has begun in Java, especially in Bogor, which has successfully introduced jack bean tempeh as a food security alternative. This product serves as a benchmark in this study, which explores its potential acceptance in Banda Aceh and Aceh Besar. The research aimed to analyze consumer preferences for jack bean-based tempeh to identify market opportunities and develop appropriate marketing strategies. Based on conjoint analysis, the most influential attribute in purchasing decisions is the product label (15.818%), followed by packaging, texture, size, certification, promotional media, point of purchase, brand, and label type. The most preferred combination includes smooth texture, banana leaf packaging, medium size, halal and BPOM certification, a traditional brand name, complete label information, sticker-type labeling, availability in traditional markets, and promotion through social media.